CALCULATION OF THE EINSTEIN COEFFICIENTS FOR CO DOPED (80 − x)Sb2O3−20Na2O−xWO3 (x% mol of WO3) GLASSES: CALCULATION OF THE EINSTEIN COEFFICIENTS FOR CO DOPED (80 − x)Sb2O3−20Na2O−xWO3 (x% mol of WO3) GLASSES - Petkova, Petya; Vasilev, Petko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
We have measured the absorption of the glasses (80−x)Sb2O3−20Na2O−xWO3 (x% mol of WO3) in the spectral regions 10 500 – 24 500 cm-1. The samples are doped with 0.05% mol of Co3O4 from x = 10% until x = 50%. The observed absorption band is due to the Co-impurity in the visible spectral region. This absorption band of glasses contains information about the exactly values of the Einstein coefficients which will be useful for their application in laser technologies.